Reorientation of desire in Adrienne Rich's Twenty-One Love Poems - Hassan, Mohamad Fleih; Talif, Rosli; Jujar Singh, Hardev Kaur (2015)
Adrienne Rich (1929-2012) is a leading voice within the feminist movement in the United States. The issue of female identity and liberation is a recurrent theme in Rich’s poetry. She proposes a new possibility of freeing women through the reorientation of female desire as a key issue in the restructure of female identity. Therefore, my objective in this study is to deal with the abject representation of female desire in Adrienne Rich’s Twenty-One Love Poems to show her poetics behind the reorientation of female desire. This paper employs Julia Kristeva’s Abjection in analyzing Rich’s Twenty-One Love Poems (1977) to explore her poetic discourse concerning the restructuring of female identity through the reorientation of female desire. Desire is a key determinant of one’s identity; thus the application of Kristeva’s theory of Abjection will give a better understanding of Rich’s resort to the reorientation of female desire as a source of empowerment for women. Rich presents her proposal of female desire as a new strategy of helping women against the oppressive thought of heterosexuality and patriarchy in her poems. Rich in this poem exhibits a transformative understanding of the potentials and powers of the female body and the possibility of utilizing it to face the compulsory heterosexuality and patriarchal thought.